Advertising in a Changing Context: McKay brand´s answer - Vergara-Leyton, Enrique; Catalán-Torres, Luis; Edwards-Correa, Cristóbal (RChD: creación y pensamiento, 2024)
This article analyzes the print advertising of the McKay brand in women’s magazines in 1967 and 1968, with Eva magazine as a reference. In particular, the research sought to identify the brand values in its advertisements in a political and economic context of deep transformations in Chilean society. McKay’s advertising was analyzed using a semiotic-oriented qualitative methodology based on the selection of an intentional sample of four ads. Among the analysis’ main results, we found that the brand’s advertising focused on two communicative dimensions: one, its capacity to face the challenge of developing products that contributed to improving customers’ quality of life and, two, its products’ attributes endorsed by its tradition in the food market. In conclusion, we can point out that McKay developed its brand values aimed at representing its modernization process in order to be in tune with the market and society’s new demands, as both were in a process of transformation through a synergistic interaction between product, quality of life and modernizing experience associated with consumption.